Exploring manager-subordinate dyads: The moderating effect of supervisory support on the relationship between work locus of control and job involvement - Christopher G. Nunns; Loukia Argirys (South African Journal of Business Management, 1992)
In this article the moderating effect of supervisory support on the relationship between work locus of control and job involvement is investigated. Seventy non-managerial banking employees constituted the sample. Using the statistical technique of Moderated Multiple Regression, results indicated high supervisory support enhances job involvement of employees with an external locus of control orientation. High supervisory support was found to inhibit involvement of employees with an internal locus of control orientation. Limitations of the results are discussed, as are implications for leadership research and practice.
Keywords: 650